One Injury, Two Tracks and Two Weapons with Two Thoughts: An Exhumation Case Report - Naveen Sharma; Kunal Khanna; Vijay Pal Khanagwal; Luv Sharma; Jitender Kumar Jakhar (Journal of Clinical and Diagnostic Research, 2023)
Exhumation is authorised digging out of already buried body from his legitimate graveyard. The autopsy in exhumed dead body require extreme attention and thorough examination of the corpse to determine the exact cause and manner of death. Exhumation also helps to evaluate and rule out any disease responsible for death. In the present case, authors discuss and report an unusual case of decomposed young adult male of 24-year-old, who was killed/stabbed by his younger brother. Body of deceased was buried by the perpetrator of crime without police information and medicolegal autopsy. The stab wound was altered by accused to misguide or create confusion in identifying the type of injury and weapon of offence. Later, this scenario was solved by autopsy surgeons after visiting incident scene, complete postmortem examination of the corpse and examinations of belongings.